Ethnic disparities in prevalence and patterns of smoking and nicotine dependence in rural southwest China: a cross-sectional study - Xu-ming Wang; Chao Wu; Allison Rabkin Golden; Cai Le (BMJ Open)
Objectives This study examines ethnic disparities in prevalence and patterns of smoking and nicotine dependence in rural southwest China.Design This was a cross-sectional design.Setting This study was conducted in rural Yunnan Province of China.Participants 7027 consenting individuals aged ≥35 years among Han majority and four ethnic minority groups (Na Xi, Li Shu, Dai and Jing Po) participated in this study. Information about participants’ demographic characteristics as well as smoking habits and an assessment of nicotine dependence with the Fagerstrom Test for Nicotine Dependence (FTND) was obtained using a standard questionnaire.Results Males had significantly higher prevalence of current smoking than females (64.8% and 44.4%, p<0.01). Among current smokers, the prevalence of nicotine dependence was significantly higher in males compared with females (19.9% and 7.1%, p<0.01). Jing Po men and women had the highest prevalence of current smokers (72.2% vs 23.1%, p<0.01), whereas the highest prevalence of nicotine dependence was found in male Dai current smokers and female Li Shu current smokers (44.8% vs 32.5%, p<0.01). Filtered cigarettes were the most popular form of tobacco used across all five ethnic groups. Over 75% of tobacco users initiated smoking and regularly smoked during adolescence, and those of minority ethnicity smoked regularly at a younger age than those of Han descent (p<0.05). Individuals in all five ethnic groups with higher levels of education had a lower probability of current smoking status (p<0.05), whereas a negative association of level of education with nicotine dependence was only observed in current smokers in the Han majority and Dai ethnic minority groups. Among Han majority current smokers, higher annual household income was associated with a higher risk of nicotine dependence (p<0.05).Conclusion Future interventions to control tobacco use should be tailored to address ethnicity and socioeconomic factors.